Health behavior and medical insurance under the healthy China strategy: a moral hazard perspective - Chen, Linhong; Zhang, Lingyu; Xu, Xiaocang (Frontiers in Public Health, 2024)
IntroductionHigh medical expenditure is one of the major obstacles to achieving common prosperity in China. As a health risk compensation and protection mechanism, medical insurance has played a good role in alleviating the economic burden of patients. However, due to the existence of moral hazard, medical insurance may also lead to the occurrence of psychological deviation and overtreatment of patients or hospitals’ health treatment expectations, thus generating unnecessary pressure on public financial expenditure.MethodsUsing the China Health and Retirement Longitudinal Survey (CHARLS) and Heckman model, this paper discusses the difference in the impact of medical insurance on outpatient and hospitalization costs. The change of the proportion of out-of-pocket medical expenditure is further analyzed.ResultsThe study found that while medical insurance reduced the probability of outpatient visits and increased the probability of hospitalization, it increased the cost of outpatient visits and hospitalization. Further, it reduces the share of out-of-pocket medical expenditure.DiscussionThis shows that medical insurance does play a role in alleviating the financial pressure of patients, but the overtreatment caused by moral hazard cannot be ignored, especially the over-examination and over-prescribing of drugs in the outpatient process.